Effects of social relations at work and support from family and friends on the consequences of inmate violence on correctional staff burnout - Isenhardt, Anna (Criminal justice and behavior, 2019)
This article explores (a) the influence of positive relationships with direct supervisors and co-workers, and feelings of support from family and friends, on burnout and the sense of security and (b) their hypothetical buffering influence on the harmful effects of being a victim of inmate violence or observing violence between inmates in a sample of Swiss correctional staff (N = 2,045). Moderated mediation path models indicated that all forms of social relationships increased the sense of security and decreased burnout. A positive relationship with direct supervisors had no significant moderating effect. A high degree of cohesion with colleagues ameliorated the adverse effects of observing violence between inmates on the sense of security and, mediated by the sense of security, on burnout. This buffering effect was only significant for male employees. Support from family and friends did not act as a buffer; on the contrary, it amplified the effects of violence.